Teaching Artists: Serving Special Education Students in Local Schools - Levitt, Roberta; Kramer-Vida, Louisa (Journal of the American Academy of Special Education Professionals, 2011)
The performing arts center of a major university has partnered with many local school districts to provide support for teaching artists who work directly with children in many diverse, co-taught classrooms. The artists were concerned with their ability to properly handle the students with special needs who are a major component of their classroom assignments. The artists completed a survey related to this concern, and self-characterized in a group setting to reinforce the fact that there is diversity in any classroom setting. The teaching artists then voiced their feelings about their special education students’ characteristics and their view of the schools’ culture in the facilities where they teach. A brief review of the literature and two professors’ personal backgrounds, expertise, and experience led to a very insightful discussion about potential solutions for the professional teaching artists’ perceived problems.